2014
DOI: 10.1021/jp5036103
|View full text |Cite
|
Sign up to set email alerts
|

Interface Optimization and Electrical Properties of 0.5Ba(Zr0.2Ti0.8)O3–0.5(Ba0.7Ca0.3)TiO3Thin Films Prepared by a Sol–Gel Process

Abstract: In this work, 0.5Ba(Zr 0.2 Ti 0.8 )O 3 −0.5-(Ba 0.7 Ca 0.3 )TiO 3 (0.5BZT−0.5BCT) thin films were synthesized at 500 °C by introducing a seed layer. Low interfacial diffusion and high (100) orientation were simultaneously achieved. Minimal leakage current density, dielectric constant, and loss were obtained owing to low crystallization temperature and low interfacial diffusion. The pyroelectric coefficient remained relatively high because of the high orientation, which resulted in superior pyroelectric figures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…8. The process starts with the preparation of the precursor solution from Ba and Sr carboxylates, usually acetates, and Zr and Ti alkoxides, mostly propoxides and butoxides (Chen et al 2016;Chi et al 2013Chi et al , 2014Huang et al 2016;Li et al 2013Li et al , 2015cLin et al 2012;Wang et al 2014aWang et al , 2015. In most of the cases, acetic acid and 2-methoxyethanol are used as solvents.…”
Section: Chemical Solution Deposition Of Bzt-bct-based Filmsmentioning
confidence: 99%
See 2 more Smart Citations
“…8. The process starts with the preparation of the precursor solution from Ba and Sr carboxylates, usually acetates, and Zr and Ti alkoxides, mostly propoxides and butoxides (Chen et al 2016;Chi et al 2013Chi et al , 2014Huang et al 2016;Li et al 2013Li et al , 2015cLin et al 2012;Wang et al 2014aWang et al , 2015. In most of the cases, acetic acid and 2-methoxyethanol are used as solvents.…”
Section: Chemical Solution Deposition Of Bzt-bct-based Filmsmentioning
confidence: 99%
“…Some groups reported the existence of a metastable pyrochlore phase (Chen et al 2016;Chi et al 2014;Kang et al 2012). Kang et al found that by modifying the solution chemistry, the fraction of the pyrochlore phase in BZT-0.5BCT films could be reduced.…”
Section: Chemical Solution Deposition Of Bzt-bct-based Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mimura et al [17] prepared BCZT thin films fabricated on Pt/TiO x /SiO 2 /Si substrates at temperatures above 650 °C, and the temperature at which the films were well crystallized was maintained at approximately 700 °C. Furthermore, for this type of film, more and more researchers have focused on interface issues [18][19][20]. Chi et al [18,19] conducted an in-depth study of BCT-0.5BZT thin films, in which they synthesized BCT-0.5BZT thin films at 500 °C by introducing The next step was to deposit BZT-0.5BCT on top of the LNO coating and pyrolyze the material at 450 °C for 120 s on a hot-plate.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, for this type of film, more and more researchers have focused on interface issues [18][19][20]. Chi et al [18,19] conducted an in-depth study of BCT-0.5BZT thin films, in which they synthesized BCT-0.5BZT thin films at 500 °C by introducing The next step was to deposit BZT-0.5BCT on top of the LNO coating and pyrolyze the material at 450 °C for 120 s on a hot-plate. These spin coating and pyrolyzation processes were repeated four times to obtain the final desired film thickness.…”
Section: Introductionmentioning
confidence: 99%